Evaluation of root canal anatomy of maxillary premolars in a North Indian subpopulation using cone-beam computed tomography - Sushila Kumari Malik; Rakesh Singla; Gurdeep Singh Gill; Namita Jain; Tarun Kumar; Suraj Arora (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the present study was to investigate the root canal anatomy of maxillary premolars in a North Indian subpopulation using cone-beam computed tomography (CBCT). Materials and Methods: CBCT images of 101 extracted maxillary first and second premolars were analyzed, and data were recorded to determine length of the tooth, number of roots, bifurcation level in double rooted teeth, number of apical foramina, and anatomy of the root canal system. Results: Most maxillary first premolars were double rooted (57.7%), while maxillary second premolars were predominantly single rooted (83.6%). The average length of the maxillary first premolar was 21.6 mm and second premolar was 21.3 mm. All double-rooted maxillary premolars had two canals. Single canal (at apex) was more prevalent in single-rooted maxillary premolars (86% in first premolar and 73% in second premolar). In double-rooted maxillary first premolar, the most prevalent canal type was Type IV (34.6%), followed by Type I (23.1%) and Type V (17.3%), and in maxillary second premolars, the dominant canal morphology was Type II (32.6%), followed by Type IV (22.4%) and Type I (20.4%). Conclusion: In North Indian subpopulation, most maxillary first premolars have double roots with two root canals, while second premolars are predominantly single rooted with single canals. Maxillary premolars can show all types of Vertucci's root canal anatomy with most prevalent being Type IV in double-rooted maxillary first premolars, Type I in single rooted maxillary first premolars, and Type II in maxillary second premolars.